MUTU GIZI DAN MUTU ORGANOLEPTIK BISKUIT KOMBINASI TEPUNG TEMPE DAN TEPUNG LABU KUNING (CUCUBITA MOSCHATA) SEBAGAI MAKANAN TAMBAHAN PENDERITA TBC - Ilham, Dezi; Harleni, Harleni; Masri, Erina (Ensiklopedia of Journal, 2021)
Tempe and pumpkin are widely available in West Sumatra. Tempe contains high protein and pumpkin contains very high iron ( Fe) and vitamin C. The purpose of this study was to determine the nutritional quality and organoleptic quality of biscuits with a combination of tempeh flour and pumpkin flour (Cucurbita Moschata) as an additional food for TB patients. This research is an experimental study using a completely randomized design (CRD) with four treatments. Treatment by combining tempe and pumpkin which is used as flour in making biscuits. The treatment and comparison of the amount of tempeh flour and pumpkin flour were A (150 g: 0 g), B (150 g: 50 g), C (150 g: 100 g), and D (150 g: 150 g). The results of this study indicate the color preference test, the average preference value of the panelists ranges from 2.78-3.02, the preference test the average aroma value is 2.68-2.98, for the preference test the texture average value is 2.66- 2.7 and the preference test for the average taste value of 2.62-2.72. Test for protein content ranged from 21.71% - 25.90%, test for iron (fe) levels 28.81 mg/kg – 36.62% mg/kg, test levels of vitamin C 0% - 1.28%. Biscuits with sample code A are biscuits with the best treatment in terms of color, aroma and taste, while in terms of texture the best treatment is biscuits with code until C. The nutritional quality test has the highest protein content in treatment D, namely 25.90%, iron content test The highest (Fe) in treatment C was 36.62 mg/kg, and the highest level of vitamin C was tested in treatment D, which was 1.28%.Keywords: Biscuits, Tempe, Pumpkin.